Microabrasion Wear Behavior of Fast-Borided Steel Tooth Drill Bits - Gunen, Ali; Kanca, Erdogan; Demir, Mehmet; Er, Yusuf; Saglam, Gokhan; Gok, M. Sabri (Taylor & Francis Inc, 2017)
In this study, the surface of steel tooth drill bits (Ni-Cr-Mo based) was subjected to the solid-state boriding treatment with 10- to 50-nm nanoboron powder. Boriding processes were carried out at a constant temperature of 1273 K for 30, 45, 60, 75, 90, and 105 min using a solid-state box boriding technique. Borided drill bit samples were characterized by conventional methods (microstructure, microhardness, X-ray diffraction, and chemical analysis). The wear behavior of borided samples was tested at different loads and sliding speeds by a microabrasion experimental setup. Metallographic studies showed that the boride layers have a sawtooth morphology and consist of FeB and Fe2B. The thickness and hardness of the boride layer were 35.29-202.56 mu m and 1300-2333 HV0.1, respectively, depending on the duration. The wear resistance of borided samples increased significantly due to the increase in surface hardness and lubricating effect, both of which were caused by the boriding process. A groove wear mechanism prevailed in borided samples, whereas that of bare steel tooth drill bits (STDBs) was grooving, rolling, and mixed.
Keywords: Coating; surfaces; hardening; wear; fast borided steel tooth drill bits